2015
DOI: 10.1097/sla.0000000000001470
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Mobilization Reduces Postoperative Mortality After Esophageal Cancer Surgery

Abstract: This all-inclusive nationwide study strongly suggests that POM is significantly reduced after LGM for EC. This is high valuable evidence that helps decision making regarding the optimal approach for EC surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 25 publications
1
38
1
4
Order By: Relevance
“…After MIE was proven to be a feasible and safe procedure over the past decade, we introduced this technique at our institution [41516]. In a case–control study of the first 62 MIE patients, we found that implementation of this approach caused no difficulties [12].…”
Section: Discussionmentioning
confidence: 99%
“…After MIE was proven to be a feasible and safe procedure over the past decade, we introduced this technique at our institution [41516]. In a case–control study of the first 62 MIE patients, we found that implementation of this approach caused no difficulties [12].…”
Section: Discussionmentioning
confidence: 99%
“…Briez et al reported that the prevalence of major pulmonary complications was significantly lower in the laparoscopic hybrid MIE group than in the open group (15.7% vs. 42.9%, respectively); the same was true for overall morbidity (35.7% vs. 59.3%, respectively) and in-hospital mortality (1.4% vs. 7.1%, respectively), with similar 2-year survival rates between the two groups (21). In a French nationwide study of approximately 3,000 patients, Messager et al compared laparoscopic gastric mobilization with open surgery; they found that the 30-day postoperative mortality was significantly lower in the hybrid (laparoscopic) group even after propensity score matching (3.3% vs. 5.9%), although they did not mention morbidity (22). More recently, Bjelovic et al confirmed some benefits of hybrid MIE as previously described and also reported that a greater number of lymph nodes were harvested from patients who underwent hybrid MIE using laparoscopy than from those who underwent open surgery (31.9 vs. 26.3, respectively) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Oshikiri et al reported that HALS had advantages in terms of less-restrictive ventilatory improvement, fewer subsequent pulmonary complications and less blood loss [8]. In French nationwide study, laparoscopic gastric mobilization in esophagectomy is significantly reduced the postoperative mortality than open gastric mobilization [23]. Usually, laparoscopic procedure related to less trauma and low blood loss in spite of longer operation time.…”
Section: Discussionmentioning
confidence: 99%